2021
DOI: 10.3174/ajnr.a7017
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Gray and White Matter Damage in Different Hereditary Spastic Paraplegia Subtypes

Abstract: BACKGROUND AND PURPOSE: Spinal cord damage is a hallmark of hereditary spastic paraplegias, but it is still not clear whether specific subtypes of the disease have distinctive patterns of spinal cord gray (GM) and white (WM) matter involvement. We compared cervical cross-sectional GM and WM areas in patients with distinct hereditary spastic paraplegia subtypes. We also assessed whether these metrics correlated with clinical parameters. MATERIALS AND METHODS:We analyzed 37 patients (17 men; mean age, 47.3 [SD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…29 While each subtype of HSP has its distinct genetic cause and pathophysiology, length-dependent axonal degeneration has been consistently found in pathologic studies, 30 and imaging studies have reported spinal cord atrophy and corticospinal tract abnormalities in a variety of HSP subtypes. [31][32][33] We therefore believe axonal degeneration and the subsequent release of NfL to be a common downstream process caused by possibly distinct upstream pathways. Nevertheless, differences in the rate of axonal decay and the involvement of additional neuroanatomical structures may lead to different sNfL levels across the subtypes of HSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 While each subtype of HSP has its distinct genetic cause and pathophysiology, length-dependent axonal degeneration has been consistently found in pathologic studies, 30 and imaging studies have reported spinal cord atrophy and corticospinal tract abnormalities in a variety of HSP subtypes. [31][32][33] We therefore believe axonal degeneration and the subsequent release of NfL to be a common downstream process caused by possibly distinct upstream pathways. Nevertheless, differences in the rate of axonal decay and the involvement of additional neuroanatomical structures may lead to different sNfL levels across the subtypes of HSP.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing our findings to results obtained by other methods, imaging studies of the spinal cord and the corticospinal tract seem most suited, as they provide crosssectional data on the course of SPG4. Several magnetic resonance imaging studies in patients with SPG4 have found atrophy of the spinal cord 31,32 or abnormalities of the corticospinal tract. 33,[35][36][37] Some of these studies have reported a correlation of disease duration and severity with the extent of corticospinal tract abnormalities on the other side.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord atrophy has been described in a few studies of SPG5 patients or other HSP subtypes [ 11 13 ]. However, only a small selection of spinal cross-sectional area or diameter were measured [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord atrophy has been described in a few studies of SPG5 patients or other HSP subtypes [ 11 13 ]. However, only a small selection of spinal cross-sectional area or diameter were measured [ 11 13 ]. To our knowledge, our study is the first one to thoroughly investigate the whole length of cervical and thoracic regions, with measurements of both cross-sectional area and antero-posterior/ transverse diameter.…”
Section: Discussionmentioning
confidence: 99%
“…This combined approach proved useful to uncover SC changes and to identify potential biomarkers in several other neurodegenerative conditions, such as Friedreich's ataxia, amyotrophic lateral sclerosis, and hereditary spastic paraplegia. [10][11][12] In the current study, our aim was to determine in vivo the pattern and extent of SC damage in RFC1-related disorder. Simultaneously, we investigated the potential clinical correlates of these neuroimaging abnormalities.…”
mentioning
confidence: 99%